Two Unusal Primary Carcinomas of the Glans Penis: Mucoepidermoid Carcinoma and Adenosquamous Carcinoma - Warnnissorn, Naree; Parichatikanond, Pisal; Ratanarapee, Samrerng; Nualyong, Chaiyong; Amesombun, Ame-on (Siriraj Medical Journal, 2003)
Two cases of rare histologic subtypes of carcinomas involving glans penis are reported. Both contained two distinct cellular differentiation, squamous cells and mucin-producing cells. The first case was a 34-year-old Thai male with chronic ulcer at penis, showing predominant squamous cell carcinoma with interspersed small sheets of mucin-producing cells without discrete glandular structure, thus designated as "muco-epidermoid carcinoma". The involved inguinal lymph node revealed both squamous and mucin-producing cells. Â Â Â Another case is a 39-year-old Thai male with penile, histologicaly proved to be carcinoma mainly constituted by malignant sqlignant part and focal glandular differentiation. The glands lined by colummer cells contained intraluminal and intracellular mucin. The bilateral sentinel lymph nodes were negative for malignancy. Â Â Â The immunoperoxidase staining for carcinoembryonic antigen was positively marked with mucin-producing cells in both cases. In addition, transmission electron microscopic study of mucoepidermoid carcinoma identified three populations of cells, namely squamous cells with tonofilament, mucin-producing cells with microvilli, and lastly intermediate cells bearing dual differentiation. Â Â Â These unusual carcinoma of glans penis are extremely rare conditions of unknown origin with a poorly defined prognosis. Discussion and review literature on the histologic definition and origin of these tumors are included.